2021
DOI: 10.20452/pamw.15823
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of rectal neuroendocrine tumors in a 13-year retrospective single-center study. Are we following the guidelines?

Abstract: INTROduCTIONRectal neuroendocrine neoplasms (rNENs) are small tumors that are currently being found at an increasing frequency during colonoscopy examinations. 1 These are usually G1 lesions, of less than 10 mm in diameter, derived from the muscularis mucosa, which grow into the submucosa and deeper layers. Their subepithelial origin is the reason why simple snare or biopsy forcep polypectomy is usually an ineffective method of treatment. Thus, more advanced methods such as endoscopic mucosal resection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
1
Order By: Relevance
“…Although the link could not be demonstrated in this study, other studies with larger sample sizes have demonstrated a definitive link between advanced endoscopic techniques and increased likelihood of R0 resection. 8,9,[14][15][16] When R0 resection is not achieved with the first procedure, repeated interventions are necessary which increases the risk of complications, patient distress and further economic burden. Overall, this highlights the need for increased endoscopist education regarding recognition of rNETs, appropriate choice of endoscopic resection technique and consideration of referral to specialist centres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the link could not be demonstrated in this study, other studies with larger sample sizes have demonstrated a definitive link between advanced endoscopic techniques and increased likelihood of R0 resection. 8,9,[14][15][16] When R0 resection is not achieved with the first procedure, repeated interventions are necessary which increases the risk of complications, patient distress and further economic burden. Overall, this highlights the need for increased endoscopist education regarding recognition of rNETs, appropriate choice of endoscopic resection technique and consideration of referral to specialist centres.…”
Section: Discussionmentioning
confidence: 99%
“…Standard polypectomy without lifting may be insufficient due to the subepithelial origin of these lesions, there is evidence for advanced endoscopic techniques including endoscopic submucosal dissection (ESD) and cap-assisted mucosal resection. 1,2,4,[8][9][10][11][12][13][14][15][16] Post endoscopic excision of rNETs, ENETS underscores the importance of distinguishing lesions based on their pathological status; be it R0, indeterminate, or R1 (any margin, even a free margin <1 mm is defined as R0). They advise that every attempt should be made to render indeterminate or R1 resected lesions R0 to reduce recurrence risk and allow for follow-up based on the R0 resection category (i.e., no follow-up for lesions <10 mm without risk factors).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in clinical practice, the correct diagnosis of RNENs at the time of the first endoscopy concerns only 18-30% of patients. Most lesions are removed incorrectly and non-radically, using a diathermy loop or biopsy forceps -the R0 resection rate is 24-30% [24,82]. It may also occur that the correct endoscopic method of NEN treatment is used but R0 resection is not achieved.…”
Section: Guidelinesmentioning
confidence: 99%
“…Jednak w praktyce klinicznej prawidłowe rozpoznanie RNEN w czasie pierwszej endoskopii dotyczy jedynie 18-30% pacjentów. Większość zmian jest nieprawidłowo i nieradykalnie usuwana, za pomocą pętli diatermicznej lub kleszczyków biopsyjnych -odsetek resekcji R0 wynosi 24-30% [24,82]. Może też wystąpić sytuacja, w której do leczenia endoskopowego NEN zastosowano technikę prawidłową, ale nie uzyskano resekcji R0.…”
Section: Leczenie Endoskopowe Crnensunclassified